Accuracy of ESAT6-CFP10 skin test compared with tuberculin skin test in a healthy population: a randomized, blind, parallel controlled phase III clinical study - Xiaoyan Ding; Weixin Du; Qiao Liu; Lifeng Tao; Yan Shao; Peng Lu; Huaiyu Yang; Xiaoxue Teng; Cheng Chen; Zhongqi Li; Jinbiao Lu; Aihua Zhao; et al. (BMC Infectious Diseases)
Abstract Background This study aimed to evaluate the diagnostic performance of ESAT6-CFP10 (EC) skin test in healthy population and determine the factors influencing the booster effect. Methods We conducted a randomized, double-blind, parallel controlled trial in healthy population. The experiment was divided into two stages. In the first stage, all participants underwent T-SPOT, TB-PPD, and EC tests. In the second stage, to evaluate whether BCG vaccination affected the efficacy of skin tests, the participants with three negative results in the first stage were randomly assigned to the BCG and placebo groups at a ratio of 2:1 and underwent three tests. The positivity rates and concordance of the three tests were calculated in both stages, and a logistic regression model was constructed to determine the factors influencing the booster effect of EC in the second stage. Safety observations were continued until the skin test results were available. Results In the first stage, 1,564 participants were enrolled in the study. The positivity rates of the T-SPOT, EC, and TB-PPD tests in all the participants were 18.89%, 10.37%, and 53.96%, respectively. The concordance between the EC and T-SPOT tests was 88.97% (kappa = 0.56), and that between the TB-PPD and T-SPOT tests was 58.19% (kappa = 0.20). In the second stage, 585 participants were assigned to the BCG or placebo group. In the BCG group, the positivity rates for the T-SPOT, EC, and TB-PPD tests were 4.76%, 7.30%, and 73.65%, respectively. The concordance between the EC and T-SPOT tests was 94.92% (kappa = 0.55), and that between the TB-PPD and T-SPOT tests was 29.84% (kappa = 0.02). In the placebo group, the positivity rates for the T-SPOT, EC, and TB-PPD tests were 6.88%, 11.88%, and 39.38%, respectively. The concordance between the EC and T-SPOT tests was 91.25% (kappa = 0.49), and that between the TB-PPD and T-SPOT tests was 66.25% (kappa = 0.17). The logistic regression model showed that age ≥ 60 years (odds ratio [OR] = 5.42, 95% confidence interval [CI]: 2.05–14.26) and retest positivity of T-SPOT test (OR = 44.87, 95% CI: 16.58–135.21) were stimulative factors of EC booster effect. Adverse reactions occurred in 168 (10.74%) and 33 participants (5.64%) in the first and second stage, respectively. Most of these were local adverse reactions, including injection site pain, pruritus, and rash. Conclusions The diagnostic performance of the EC skin test was similar to that of the T-SPOT test in the healthy population and was unaffected by BCG vaccination. The booster effects were more inclined to occur in population with retest positivity of T-SPOT or age ≥ 60 years. Clinical trials Registration NCT02795260, Clinical Study of Recombinant Mycobacterium Tuberculosis Allergen ESAT6-CFP10 on Healthy People Aged 18–65(III-healthy), Registration Date: June 10, 2016.